Trust in things: A review of social science perspectives on autonomous human-machine-team systems and systemic interdependence - Akiyoshi, Mito (Frontiers in Physics, 2022)
For Autonomous Human Machine Teams and Systems (A-HMT-S) to function in a real-world setting, trust has to be established and verified in both human and non-human actors. But the nature of “trust” itself, as established by long-evolving social interaction among humans and as encoded by humans in the emergent behavior of machines, is not self-evident and should not be assumed a priori. The social sciences, broadly defined, can provide guidance in this regard, pointing to the situational, context-driven, and sometimes other-than-rational grounds that give rise to trustability, trustworthiness, and trust. This paper introduces social scientific perspectives that illuminate the nature of trust that A-HMT-S must produce as they take root in society. It does so by integrating key theoretical perspectives: the ecological theory of actors and their tasks, theory on the introduction of social problems into the civic sphere, and the material political economy framework developed in the sociological study of markets.